Brayton’s subatmospheric inverse cycle with regeneration of output heat by Maisotsenko’s cicle - Khalatov, А. А.; Severin, S. D.; Brodetsky, P. I.; Maisotsenko, V. S. (Reports of the National Academy of Sciences of Ukraine, 2015)
The novel thermodynamic cycle with a high regeneration rate using a solar energy and the environment energy in the form of a psychrometric temperature difference is considered. The primary cycle feature is the high thermal efficiency exceeding significantly the efficiency of gas turbines, based on the Brayton cycle. It is shown that, at the low turbine power (up to 10 kW), this unit can operate using only the psychrometric and solar energies for the electricity production.